INTELLECTUAL HUMILITY AS STRENGHT IN THE PROCESSES OF THE FORMATION AND DEVELOPMENT OF KNOWLEDGE - Gudeliauske, Gintare (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The aim of the research: To describe the intellectual humility of a teacher as strength in the processes of forming and developing knowledge. Intellectual virtues presuppose the objective of deep, factual perception with a possibility to make mistakes. A lot of pedagogues lack the activities important for virtues without dependence on mood or similar supporting means (the total level of virtue).  A teacher who distinguishes with intellectual humility, who belongs to the virtues of the first range (the initiation of learning process and its guiding towards the right direction) and has connection with other intellectual virtues, aims for coordinated learning relationship where the sense of equality is present, as well as broaden perspective, distinguishes with flexibility while re-considering convictions, fear which is felt by an intellectually humble person when he/she misses information or something is not understood. An intellectually humble teacher, developing his/her knowledge, distinguishes with the constant pursuit for development, ability to self-evaluate strengths and weaknesses, seeing relationship with others as perspective for development The definition of intellectual humility is usually related with the recognition that your convictions and opinions can be wrong. This virtue is concerned with the strengths of a teacher. Being an intellectually humble person opens possibilities to the independence of a learner while forming or developing knowledge and understanding. In this process the potential of colleagues is recognized, strong and weak points are firmly pointed out, intellectual arrogance is avoided.  This presupposes more possibilities for the change of learning both to a learner and the one dependant on him/her.